Microbial fermentation optimization to increase glucomannan content in porang flour with a mixed-level factorial design - NATHAN ALTHEA SANDJAJA; NEIL PRIHARTO; RIZKITA RACHMI ESYANTI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sandjaya NA, Priharto N, Esyanti RR. 2025. Microbial fermentation optimization to increase glucomannan content in porang flour with a mixed-level factorial design. Biodiversitas 26: 6541-6559. Porang (Amorphophallus muelleri) flour is a promising source of glucomannan, a polysaccharide widely applied in food, pharmaceutical, and industrial sectors. However, its use is limited by the presence of starch and calcium oxalate impurities, which degrade product quality and safety. Conventional purification methods, such as mechanical separation, solvent extraction, and enzymatic treatment, can improve glucomannan content but are constrained by cost, chemical residues, or low efficiency. This study aimed to develop a sustainable microbial fermentation to enrich glucomannan and reduce oxalate content. Four α-amylase producers (Bacillus subtilis, Bacillus cereus, Aspergillus niger, and Aspergillus oryzae) were evaluated. Optimization to increase glucomannan content was conducted using a Mixed-Level Factorial Design (MLFD) with varying concentrations of substrate, inoculum, and microbial species. Microbial growth kinetics and α-amylase activity profiles were monitored to determine fermentation efficiency, while statistical modeling was applied to identify significant factors influencing glucomannan yield. The findings showed that the optimum conditions, with the highest increase in glucomannan and calcium oxalate content, were achieved with B. subtilis at a substrate concentration of 4% (w/v) and an inoculum concentration of 1% (v/v). These findings demonstrate that microbial fermentation with B. subtilis provides an eco-friendly and cost-effective alternative to chemical and enzymatic extraction for glucomannan enrichment. It has the potential to scale as a sustainable processing method to support the increased value-added valorization of porang as a strategic Indonesian commodity.